PFM.28 What can we tell parents about the outcomes of arthrogryposis?. (9th June 2014) - Walker, L; Splitt, M; MacPhail, S
Abstract : Arthrogryposis is a complex diagnosis which may result in significant disability due to mobility problems or neonatal mortality due to pulmonary hypoplasia. Long term outcomes are difficult to predict. Antenatal information was collected retrospectively from a variety of regional validated databases. Follow up data was obtained from post mortem reports and regional clinical genetics patient case files. Results: 71 cases of arthrogryposis were identified between January 1998 and December 2013, 1 was excluded. 31 cases were not diagnosed antenatally, of whom 27 are still alive. Follow up information is available for 16 patients, all of whom are reported to have normal cognitive development and different degrees of motor disability. Of the 39 cases diagnosed antenatally, 25 were terminated following counselling. 10 had additional anomalies including microcephaly, venticulomegaly, cystic hygroma, hydrops, gastroschisis and Dandy Walker malformation. 14 patients had an antenatal diagnosis and continued their pregnancy. 43% had an adverse outcome to their pregnancy. (4 neonatal deaths, one baby remains ventilated and one death in utero). One of the neonatal deaths had clear evidence of fetal activity and breathing in utero and the baby who is alive but ventilated never showed breathing movements in utero but cried at birth. Of the 8 babies still alive 3 are known to attend mainstream school. Conclusion: Predicting outcome following diagnosis of arthrogryposis is difficult. Presence of fetal activity and breathing movements on antenatal scan does not appear to be a useful prognostic feature.